Krüppel-like family of transcription factors: an emerging new frontier in fat biology - Christopher W. Brey, Mark P. Nelder, Tiruneh Hailemariam, Randy Gaugler, Sarwar Hashmi (International Journal of Biological Sciences, 2009)
In mammals, adipose tissue stores energy in the form of fat. The ability to regulate fat storage is essential for the growth, development and reproduction of most animals, thus any abnormalities caused by excess fat accumulation can result in pathological conditions which are linked to several interrelated diseases, such as cardiovascular diseases, diabetes, and obesity. In recent years significant effort has been applied to understand basic mechanism of fat accumulation in mammalian system. Work in mouse has shown that the family of Krüppel-like factors (KLFs), a conserved and important class of transcription factors, regulates adipocyte differentiation in mammals. However, how fat storage is coordinated in response to positive and negative feedback signals is still poorly understood. To address mechanisms underlying fat storage we have studied two Caenorhabditis elegans KLFs and demonstrate that both worm klfs are key regulators of fat metabolism in C. elegans. These results provide the first in vivo evidence supporting essential regulatory roles for KLFs in fat metabolism in C. elegans and shed light on the human counterpart in disease-gene association. This finding allows us to pursue a more comprehensive approach to understand fat biology and provides an opportunity to learn about the cascade of events that regulate KLF activation, repression and interaction with other factors in exerting its biological function at an organismal level. In this review, we provide an overview of the most current information on the key regulatory components in fat biology, synthesize the diverse literature, pose new questions, and propose a new model organism for understanding fat biology using KLFs as the central theme.